Automated detection and characterization of SPIO-labeled cells and capsules using magnetic field perturbations - Mills, Parker H. (2011)
Understanding how individual cells behave inside living systems will help enable new diagnostic tools and cellular therapies. Superparamagnetic iron oxide (SPIO) particles can be used to label cells and theranostic capsules for non-invasive tracking using MRI. Contrast changes from SPIO are often subtle relative to intrinsic sources of contrast, presenting a detection challenge. Here we describe a versatile post-processing method, called Phase map cross-correlation Detection and Quantification (PDQ), that automatically identifies localized deposits of SPIO, estimating their volume magnetic susceptibility and magnetic moment. To demonstrate applicability, PDQ was used to detect and characterize SPIO-labeled magnetocapsules implanted in porcine liver and suspended in agarose gel. PDQ was also applied to mouse brains infiltrated by MPIO-labeled macrophages following traumatic brain injury (TBI); longitudinal, in vivo studies tracked individual MPIO clusters over three days, and tracked clusters were corroborated in ex vivo brain scans. Additionally, we applied PDQ to rat hearts infiltrated by MPIO-labeled macrophages in a transplant model of organ rejection. PDQ magnetic measurements were SNR-invariant for images with SNR>11. PDQ can be used with conventional gradient-echo pulse sequences, requiring no extra scan time. The method is useful for visualizing biodistribution of cells and theranostic magnetocapsules, and for measuring their relative iron content.